2017
DOI: 10.1177/0363546517716632
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral Joint Loads During Running at the Time of Return to Sport in Elite Athletes With ACL Reconstruction

Abstract: Altered levels of patellofemoral stress in the ACLR knee during running may predispose individuals to patellofemoral joint pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 31 publications
1
25
2
Order By: Relevance
“…In addition, our PFJ contact force estimates for both limbs were within the range of published results (4.5-11.1 BW) for running studies in which joint moments, instead of explicitly calculated muscle forces, were input into the PFJ model. 6,18,26,39,40…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our PFJ contact force estimates for both limbs were within the range of published results (4.5-11.1 BW) for running studies in which joint moments, instead of explicitly calculated muscle forces, were input into the PFJ model. 6,18,26,39,40…”
Section: Discussionmentioning
confidence: 99%
“…36 However, limited research has been performed to assess the effect of ACLR on lower limb biomechanics during running. Available studies have reported lower knee flexion angles, knee range of motion, and knee extension moments, 26,34,43 together with increased knee external rotation 45,46 and anterior tibial translation 46 up to 12 months postoperatively. Only 2 studies to date have investigated PFJ loads during running after ACLR surgery.…”
mentioning
confidence: 99%
“…[5][6][7][8] Biomechanical differences between limbs after ACLR have been found in variables relating to the knee during gait, running and jumping tasks principally relating to knee extension moments and vertical ground reaction forces. [9][10][11][12] Previous research has suggested that biomechanical variables captured during double-leg drop jumps (DLDJ) may predict primary anterior cruciate ligament (ACL) injury as well as secondary injury, 13,14 however the primary injury analysis was in female athletes only. Biomechanical variables both proximal and distal to the knee (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the absence of anterior interval scar, load in the patellofemoral joint is increased after ACL reconstruction. 7 However, scarring of the anterior interval can cause patella baja and may lead to patellofemoral arthritis. 5 The rate of patella baja after autogenous patellar tendon ACL reconstruction has been reported to be as high as 76% in 1 case series.…”
Section: Discussionmentioning
confidence: 99%